Catalytic hydrodeoxygenation of guaiacol for organosolv lignin depolymerization – Catalyst screening and experimental validation. (15th October 2019) - Tymchyshyn, Matthew; Yuan, Zhongshun; Zhang, Yongsheng; Xu, Chunbao Charles
Highlights: The hydroprocessing of lignin reduces molecular weights and oxygen contents. Effective and inexpensive catalysts were studied during the hydroprocessing. The effectiveness of MoRu/C was studied using guaiacol as a model compound. Process parameters were investigated to determine the optimal reaction conditions. The depolymerized organosolv lignin achieved significantly reduced molecular weight. Abstract: The increasing concerns on energy demand and sustainability have intensified the development of alternatives to fossil resources. Lignin from lignocellulosic biomass can be a sustainable resource for chemicals and materials. The main challenge in lignin utilization is the large molecules with low heating values and low reactivity. Accordingly, the catalytic hydroprocessing of lignin aiming to reduce their molecular weights and oxygen contents is of great significance. Targeting at the development of effective and inexpensive catalysts for hydroprocessing and depolymerization of lignin to produce chemicals and fuels, screening of catalysts was performed followed by experimental validation. This work studied the effectiveness of MoRu carbon-supported catalysts in the hydroprocessing of guaiacol, a model compound, and organosolv lignin. Catalysts supported by different carbon materials were prepared and their effectiveness in guaiacol conversion was evaluated. Process parameters were adjusted to determine the optimum reaction conditions. This study demonstrated that the type of carbon support used to prepare Ru catalysts is an important factor in guaiacol conversion. The optimization study revealed that temperature and initial hydrogen pressure have a much greater effect on guaiacol conversion than reaction time does. The catalysts were able to greatly decrease the molecular weight of the organosolv lignin from ∼2600 to 460 g/mol at 340 °C with the most effective MoRu/AC catalyst.